Bin Nasr, Muhammad. “Political Change: Between Neglected Questions and the Current Reality,” Year 4, Issue 15 (Winter 1419 AH/ 1999 CE), Pp. 51-72. - بن نصر محمد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 1999)
Muhammad Bin Nasr’s article traces the evolution of contemporary Islamic thought with respect to the subject of the nation-state and social change. It highlights the historical paradox that has engulfed the Muslim mindset since what is referred to as the revival period in the Muslim world, when the state clashed with society. It explains the concept of change and its impact on the rise of civilizations, the state in reformist thought, and the legal and social necessity for authority. It discusses Oriental despotism between truth and exaggeration, the emergence of the state in the West, the make-up of the state and its development in contemporary Muslim literature, and addresses some of the illusions lingering in the minds of educated elites, such as the illusion of neutrality, personal choice, and natural inevitability. It concludes with an attempt to achieve stability between the state and society.